Economic potential of the Spanish language: language as a source of capital and jobs - Natalia Tsareva (Ибероамериканские тетради)
The article is devoted to the study of the economic potential of the Spanish language, language that speak 500 million people in the modern world. The growing economic value of the Spanish language is determined by two main factors: rst, the process of economic, political and cultural globalization, and second, the development of the information society and its main attribute - the Internet.